Blogging in the bush: using social computing to enhance adult literacy in remote Western Australia - Smith, Melanie; Trinidad, Sue; Biemmi Beurteaux, E. (Australian Council for Computers in Education, 2008)
The aim of this project was to investigate how the use of social computingmight enhance the effectiveness of learning for Aboriginal students living in ageographically isolated region. The case study site is a small town in the vastKimberley region of WA. As with many other outback towns, education in thiscommunity is a major issue of concern, in particular regarding theengagement of learners with educational programs. This project set out tofirst enable a group of adult literacy learners to use a social computingtool—in this case Blogging—and then to observe and evaluate the ways inwhich, and the extent to which, using this technology impacted on theirengagement with learning. The paper describes how the project wasestablished, illustrating the unique context in which the study took place; itoutlines some of the challenges faced by participants and researchers; and ittells how the project impacted on everyone involved. The findings indicatethe potential for social computing to be an extremely powerful educationaltool for Aboriginal learners and their teachers.